Tension-Free Vaginal Tape Failure After Robotic Sacrocolpopexy and Tension-Free Vaginal Tape for Concomitant Prolapse and Stress Incontinence. Issue 1 (January 2016) - Osmundsen, Blake; Gregory, W. Thomas; Denman, Mary Anna; Adams, Kerrie; Edwards, Renee; Clark, Amanda
Abstract : Obstet Gynecol Surv 2016;71(1):19–20 There is a 20% lifetime risk of undergoing surgery for stress urinary incontinence (SUI) or pelvic organ prolapse (POP) among women in the United States. These conditions often coexist, and treatment at the same time for both is often undertaken.